Intelligent surfaces in biotechnology : scientific and engineering concepts, enabling technologies, and translation to bio-oriented applications - Textor, Marcus; Grandin, H. Michelle (Hoboken, N.J. : John Wiley & Sons, 2012)
'This resource gives a comprehensive overview of surface modifications for applications in biotechnology using intelligent coatings. The coverage includes chemical properties, characterization methods, coating techniques, state-of-the-art examples, and an outlook on the promising future of this technology. It enables the interested materials scientist, chemist, or engineer to gain a comprehensive overview of the field, highlighting applications, with each chapter written by an expert in that particular area. Applications covered include tissue engineering, biotribology, drug targeting and delivery, wound healing, biosensors, nanopatterning, and bioinspired design of new smart materials and surfaces'--
'This book gives a comprehensive overview of surface modifications for applications in biotechnology using intelligent coatings from metals to plastics, including materials chemical properties, characterization methods, coating techniques, state-of-the-art examples, and an outlook on the promising future of this technology. It enables the interested materials scientist, chemist, or engineer to gain a comprehensive overview of the field, highlighting applications of high-impact, with each chapter being written by an expert in that particular area'--
Includes bibliographical references and index.
Keywords: Biomedical materials; Biotechnology -- Materials; Smart materials; Surfaces (Technology)